Spectral Properties of Silica Sol, Gel and Aerogel Doped with Metal Ions and Laser Dyes - A. Anaz, Mohammed; F. Al-sharuee, Israa (International Research Journal of Multidisciplinary Technovation, 2024)
For the purpose of this investigation, a lower hydrophobic silica aerogel was synthesized. Following doping with metal ions (CuCl) and AgCl, as well as laser dyes fluorescein and coumarin, the produced silica was transformed from a sol-gel to an aerogel throughout the process. Under the conditions of ambient pressure drying, the structure of silica aerogel has been described. Further, the modification began with Sol and culminated in the production of aerogel with the use of trimethylchlorosilane (TMCS) and hexane as solvent components. In the research, the influence of doping with dyes and metal ions on morphological and physical characteristics was investigated. The results showed that the aerogel that was generated after being doped with metal ions and laser dyes had superior physical qualities, including reduced volume shrinkage and decrease in density. The technique of spectroscopy for the purpose of analyzing the variance in chemical bonding, Raman and fluorescence were applied. field emission scanning electron microscopy (FESEM) and surface topography examination (AFM) were used to establish the hydrophobicity property. Fourier transform infrared spectroscopy (FTIR) was used to confirm the hydrophobicity property. Furthermore, the findings demonstrated that aerogels had outstanding performance in a wide variety of physical attributes. The Raman spectra of samples of sol, gel, and aerogel showed a greater degree of variation in the areas of the peaks and the manner in which they were distributed on the spectrum. Additionally, the homogeneities and nanostructures manifested themselves more prominently.